A SERVICE QUALITY, PRICE, CUSTOMER SATISFACTION AND WORD OF MOUTH IN HOSPITAL X OUTPATIENT SERVICES - Felicia Indriana; Tantri Yanuar Rahmat Syah; C.S.P. Wekadigunawan (Universitas Muhammadiyah Kalimantan Timur, 2021)
Customer satisfaction is an important factor that the hospital needs to pay attention to, because satisfied customers will tell their experience of being treated at the hospital, and invite their families and friends to take part in using the hospital's services, or commonly known as word of mouth. Complaints from outpatients at hospital X regarding the length of waiting time and prices provided, is a form of lack of customer satisfaction. The aim of this study is to determine the effect of service quality and price on customer satisfaction, and customer satisfaction with word of mouth. This research is an associative quantitative study, carried out by cross-sectional survey / cross-section of 155 respondents. Data analysis was performed using Structural Equation Modeling (SEM). The results of this study indicate a correlation between service quality and customer satisfaction, a correlation between price and customer satisfaction, and a correlation between customer satisfaction with word of mouth. These findings indicate that by improving the quality of hospital services, and providing appropriate prices, customer satisfaction will increase, which will also contribute to increased word of mouth.